Pengaruh Kualitas Layanan, Persepsi Harga, Kualitas Produk dan Citra Merek terhadap Kepuasan Konsumen : Studi pada Konsumen Pembeli dan Pengguna Produk Merek Jims Honey - Mela Arum Agustina; Alimuddin Rizal Rivai (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to determine and analyze the influence of service quality, price perception, product quality, brand image on customer satisfaction with Jims Honey brand products. This research uses an explantive quantitative research method by distributing questionnaires to several WhatsApp, Telegram, Facebook and Instagram groups. The population in this study were respondents who had purchased and used Jims Honey products directly. The data analysis method used is multiple linear regression using SPSS version 25. This test uses four independent variables, namely Service Quality, Price Perception, Product Quality, and Brand Image and Customer Satisfaction as dependent variables. The results of this research are 1) Service Quality has a positive and significant effect on consumer satisfaction for Jims Honey products. 2) Price Perception has a positive and significant effect on consumer satisfaction for Jims Honey products. 3) Product Quality has a positive and insignificant effect on consumer satisfaction. 4) Brand Image has a positive and significant effect on consumer satisfaction. 5) Service Quality, Price Perception, Product Quality and Brand Image on consumer satisfaction for Jims Honey products.